Antracycline Induced Early Onset Chronic Cardiotoxicity in Cancer Patients - Idrees, Ibtisam; Ahmad, Riaz; Nadeem, Muhammad; Khan, Amjad; Gilani, Atifa; Khattak, Rahimullah (Pakistan Armed Forces Medical Journal, 2024)
Objective: To assess the patients for early onset chronic cardiotoxicity who have been taking anthracyclines as part of their cancer treatment.Study Design: Comparative cross-sectional study.Place and Duration of Study: Oncology department, Combined Military Hospital, Rawalpindi Pakistan, from Dec 2020 to May 2021.Methodology: One hundred patients with solid or hematological malignancies taking anthracyclines for more than three months and less than a year were included in the study. They underwent 2 dimensional echocardiography by consultant cardiac physician to look for cardiotoxicity. Cardiotoxicity was defined as left ventricular ejection fraction less than 60%. Age, gender, duration of anthracyclines use and presence of comorbid illness were correlated with presence of early onset chronic cardiotoxicity in our study participants.Results:  Out of 100 cancer patients using anthracyclines for more than three months and less than 12 months included in the study, 55(55%) were males while 45(45%) were females. Sixty-nine (69%) had ejection fraction more than 60% on echocardio-graphy while 31(31%) had